Experimental demonstration of indoor sub-decimeter accuracy VLP system using differential PDOA - Zhang, Sheng (2020)
In this letter, we for the first time experimentally demonstrate a sub-decimeter accuracy visible light positioning (VLP) system using a modified phase difference of arrival (PDOA) algorithm, i.e., differential PDOA (DPDOA). Compared with the conventional PDOA algorithm where local oscillators (LOs) are used at the receiver side, the DPDOA algorithm does not require LOs by using the differential phase difference method. Moreover, Kalman filtering is used to reduce the variation of distance difference estimation and neural network is also adopted for mitigating the position shifting error caused by the nonuniform initial time delay pattern of the off-the-shelf LEDs. Experimental results show that the proposed VLP system achieves an average root-mean-square positioning error (RMSPE) of 1.8cm and a maximum RMSPE of 8 cm with a coverage of 1×1.2m2 and a height of 2m.